List of Trade Unionists & Labour Party Members [International Brigade]
1937 034-0192-005 3. A.Muir London 156 Dependant: E. Osbourne Lambeth Br. Building Section Dependant: I. Pugh Liverpool 5/12 Docks section A. Selmes Lambeth 1/56 Dependant: Mrs. Selms, 63 Maydwell St., S.E.5 (£2-0-0) T. Smith Birkenhead Dependant: E. Sines Battersea 1/425 Dependant: G. Shaw Maryhill Br. Dependant: Mrs. Shaw, 34 Seamore St., Glasgow N.W. (£2-0-0) B. Sturges Smith Square Br. London S.W. Dependant: F. Thomas Gillingham 1/666 Dependant: National Union of Rlymen. G.Leeson Covent Garden Br. Vice Chair Pol. Cte. Also LDC Del. Dependant: C. Lawther Hexham Br. Dependant: Mrs. Lawther, 30 Denmark St., Gateshead-on-Tyne (10/-) F. Plumb Covent Garden Br. Dependant: A.E.U. W.Benson Patricroft 3. Dependant: J.Campbell Finnieston Br. (Glasgow) Dependant: Mrs. J. Campbell, 5 Richard St., Glasgow C.3 (£1-15-0) P.Caplin Burnt Oak Dependant: H. Docherty Luton 4 Dependant: 292/946/34/193(iii)